Adopting early intervention for substance use disorders: a preliminary study of primary healthcare professionals in New York State. (2nd November 2018) - Yu, Jiang; Harris, Brett; Shi, Junrong
Abstract: Aims : Research has reported a lack of practice of early intervention for substance use disorders among primary healthcare professionals, and only a fraction of patients were asked about their substance use when visiting a primary healthcare office. This study examines conditions that may influence the adoption of early intervention [i.e., screening, brief intervention and referral to treatment (SBIRT)] among primary healthcare professionals. Methods : A pilot survey was emailed to primary care physicians, nurse practitioners, and physician assistants in New York State, and 248 recipients responded to the survey. Findings : Three areas appear to be associated with the adoption of SBIRT: percentage of respondents' patients using marijuana (β = 0.14; p < 0.05); perceived ability to perform intervention (β = 0.32; p < 0.05); and perception of early intervention as a responsibility of primary care professionals (β = 0.29; p < 0.05). Conclusions : Training and education to promote SBIRT for primary care workers should focus on increasing their favourable attitudes towards the intervention as a strategy of preventive medicine and include the knowledge of the infrastructure of services for substance use disorders, especially for medical providers who see large numbers of patients at a high risk for alcohol and drug misuse.